Bilateral Ureterovesical Rupture Complicating Total Hysterectomy with Ureteral Neoimplantation for Placenta Accreta Spectrum in a Preterm Multigravida: A Case Report - Afif Naufal Akbarsyah; Abarham Martadiansyah (Media of Health Research, 2026)
Placenta accreta spectrum (PASD) is an increasingly common obstetric condition that carries a substantial risk of life-threatening hemorrhage and urinary tract injury, particularly when cesarean hysterectomy is required. We reported a 28-year-old multigravida (G2P1A0) with one previous cesarean delivery who presented at 25 weeks of gestation with recurrent antepartum bleeding and marginal placenta previa. Antenatal sonography yielded a Placenta Accreta Index of 6 (probability of invasion approximately 69%) and an ISUOG score above 3, while magnetic resonance imaging suggested percreta infiltrating the rectosigmoid wall. Because of massive bleeding and threatened maternal and fetal deterioration, an emergency cesarean delivery followed by total abdominal hysterectomy was performed without prior ureteral stenting. During dissection of dense parametrial adhesions, bilateral ureteral ruptures occurred, which were repaired by extravesical ureteral neoimplantation using the Lich-Gregoir technique with double-J stenting. Histopathology confirmed PASD grade II (revised FIGO). The patient later developed a suspected vesicovaginal fistula during follow-up. This case underscored that antenatal diagnosis, multidisciplinary planning, and pre-emptive urological mapping are essential to minimize urinary tract injury in PASD surgery, and that the urological consequences of emergency hysterectomy can be considerable.